Crossbreeding: implications for dairy cow fertility and survival. (30th April 2014) - Buckley, F.; Lopez-Villalobos, N.; Heins, B. J.
<x content-type="archive" xml:space="preserve">Abstract</x> In pasture-based seasonal calving systems, failure to become pregnant during the breeding season results in important economic losses as maximum profit is attained by minimising costs and increasing the proportion of grass in the diet of the lactating dairy cow. In the United States, dairy producers primarily strive to maximise production potential but are becoming increasingly aware of the economic consequences of sub-optimal cow fertility and survival. For this reason, interest in crossbreeding is emerging. The objective of this paper is to review the fertility and survival outcomes reported from recent research studies and data analyses in Ireland, New Zealand and the United States. Research conducted in Ireland during the early 2000s concluded that of three 'alternative' dairy breeds the Norwegian Red was most suited to seasonal grass-based production. A key finding was favourable fertility and survival. A follow-up study confirmed a fertility advantage with Norwegian Red×Holstein-Friesian compared with Holstein-Friesian: proportion pregnant to first service; +0.08 and in-calf after 6 weeks breeding; +0.11. Another study found higher fertility with Jersey crossbreds: pregnant to first service; +0.21, and in-calf after 6 weeks breeding; +0.19. Studies conducted in Northern Ireland also found superior fertility performance with Jersey crossbred cows offered low and moderate concentrate diets. In New Zealand, crossbred dairy cattle (primarily Jersey×Friesian) are achieving similar rates of genetic gain for farm profit as the purebred populations, but creating additional gain derived from economic heterosis. In the United States, analysis of commercial data from California showed higher first-service conception rates for Scandinavian Red×Holstein (+6 percentage units) and Montbeliarde×Holstein (+10 percentage units) compared with Holstein (23%). They also exhibited fewer days open and greater survival. At Penn State University, Brown Swiss×Holstein cows had 17 fewer days open than Holstein cows during first lactation, and numerically fewer in second (12 days) and third lactation (6 days). At the University of Minnesota, crossbred cows had 21 percentage units higher first-service conception rates, 41 fewer days open and 12 percentage units higher in-calf rates compared with pure Holstein cows. They also had greater survival to second (+13 percentage units), third (+24 percentage units), fourth (+25 percentage units) and fifth (+17 percentage units) lactation. The literature clearly illustrates favourable animal performance benefits from crossbreeding, using a range of modern breeds, and within the context of both grass-based and high-input confinement production environments. Economic analyses generally indicate profitable performance owing to lower replacement cost and higher herd productivity.